THE EFFECT OF RETURN ON EQUITY AND INVESTMENT OPPORTUNITY SET TO PRICE EARNING RATIO WITH CURRENT RATIO AS A MODERATING - Sri Fitri Wahyuni S.E., M.M (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aims to empirically examine the effect of return on equity and investment opportunity set on price earnings ratio with the current ratio as a moderating variable. The dependent variable in this study is the price earnings ratio. While the independent variable is retrun on equity and investment opportunity set. Current ratio as a moderating variable. This population is 16 metal companies listed on the Indonesia Stock Exchange in the period 2013-2017. Sample selection technique using purposive sampling method. Based on the criteria obtained, there were 11 manufacturing companies which were the research samples. The data analysis techniques used are multiple, residual, and Moderated Regression Analysis (MRA) regerations. To obtain the data needed in this study, the author uses documentation techniques from data published by the company from the official IDX website www.idx.co.id. As well as annual reports owned by the company.The data analysis technique in this study is using path analysis, classical assumption test, hypothensic testing, t-test, f-test, coefficient of determination, moderation regression analysis, resedual test which is processed using SPSS version 16. The results of this study shows that retrun on equity has a positive and significant effect on price earnings ratio. The investment opportunity set has a negative effect on price earnings ratio. With MRA analysis, the current ratio is able to moderate the effect of return on equity on price earnings ratio. Current ratio is able to moderate the effect of investment opportunity set on price earning ratio.